Security in understanding Susan Strange´s views on the international scenario - Garay Vera, Cristián (Estudios Internacionales, 2011)
After examinig key aspects of Susan Strange´s analysis of international economic policy, which emphasizes changes in the concept of power international business negotiations as «policy» and pressures imposed by technologies on markets and the relevant actors, the article suggests that they may marginally affect security studies and analyses, particularly vis à vis problems faced by states following reforms of the nineties.